Optimized build orientation of additive manufactured parts for improved surface quality and build time - Delfs, Patrick; Tows, Marcel; Schmid, Hans-Joachim (Additive Manufacturing)
The layered structure of Additive Manufacturing processes results in a stair- stepping effect of the surface topographies. In general, the impact of this effect strongly depends on the build angle of a surface, whereas the overall surface roughness is additionally caused by the resolution of the specific AM process. The aim of this work is the prediction of the surface quality in dependence of the building orientation of a part. These results can finally be used to optimize the orientation to get a desired surface quality. As not all parts of the component surface are equally important, a preselection of areas can be used to improve the overall surface quality of relevant areas. The model uses the digital AMF format of a part. Each triangle is assigned with a roughness value and by testing different orientations the best one can be found. This approach needs a database for the surface qualities. This must be done separately for each Additive Manufacturing process and is shown exemplarily with a surface topography simulation for the laser sintering process.

Extended Analysis of the Surface Topography of Laser Sintered Polymer Parts - Delfs, Patrick; Schmid, Hans-Joachim (Fraunhofer Direct Digital Manufacturing Conference)

Thermal properties of polyamide 12 powder for application in laser sintering - Josupeit, Stefan; Schmid, Hans-Joachim (International Congress on Particle Technology (PARTEC))

Dimensional accuracy of polymer laser sintered parts: Influences and measures - Josupeit, Stefan; Delfs, Patrick; Lieneke, Tobias; Adam, Guido; Gessler, Monika; Pfisterer, H.; Schmid, Hans-Joachim (Rapid Tech - International Trade Show & Conference for Additive Manufacturing)
In the polymer laser sinter process, part quality depends on many influencing factors along the process chain. For application of the technology in series production and an integration of laser sintered parts into a technical environment, the dimensional accuracy of parts has to be taken into account. Therefore, occuring deviatons and their scattering have to be reduced and homogenized based on process parameters and build job layout. In this work, the dimensional accuracy of laser sintered parts is analyzed for varied parameter values. Influences of different process and geometrical build job parameters on dimensional deviatons are figured out. The experimental results allow an evaluation of more and less important influences. Finally, measures are deduced to reduce and homogenize dimensional deviations.

Funktionsintegration additiv gefertigter Dämpfungsstrukturen bei Biegeschwingungen - Künneke, Thomas; Zimmer, Detmar (DVM Tagung - Additiv gefertigte Bauteile und Strukturen)
Additive manufacturing processes offer great freedom in the design of components. This enables a high level of function integration. Also in terms of vibration damping, additive manufacturing yields opportunities for the selective implementation of damping functions due to their characteristics. In powder-based processes the disperse support material can be kept inside the cavities of the structure. This powder material can act as a particle damper. Due to the freedoms in design, the damping behavior can be adjusted selectively by varying the geometrical features of the cavities. Within this paper, investigations on the damping behavior of additive manufactured parts regarding free bending vibrations are focused.

Additive Manufacturing of a Lightweight Rotor for a Permanent Magnet Synchronous Machine - Lammers, Stefan; Adam, Guido; Schmid, Hans-Joachim; Mrozek, Rafael; Oberacker, Rainer; Hoffmann, Michael; Quattrone, Francesco; Ponick, Bernd (EDPC 2016)
Additive Manufacturing (AM), also known as 3D printing, is a relatively new technology which enables the toolless production of components and entire assemblies directly from a CAD file. Today, the technology is still not widely used in industrial production. It is mainly limited to special applications, although it shows great potential. In this paper, first approaches are shown to apply AM to the production of rotors for permanent magnet synchronous machines (PMSM). The possibilities of a lightweight design with a low moment of inertia as well as the influence on the magnetic anisotropy for an improved sensorless control of PMSM are pointed out. The results clearly demonstrate the great potential of additive manufacturing in electrical engineering applications.

Influences on the dimensional Accuracy of Laser Sintered Parts along the Process Chain - Josupeit, Stefan; Delfs, Patrick; Lieneke, Tobias; Schmid, Hans-Joachim (27th Annual International Solid Freeform Fabrication Symposium)

Dimensional tolerances for additive manufacturing: Experimental investigation of manufacturing accuracy for selective laser melting - Lieneke, Tobias; de Groot, Stefan; Adam, Guido; Zimmer, Detmar (ASPE 2016 Summer Topical Meeting)

Reproducibility of the Dimensional Accuracy - Investigations for FDM - Knoop, Frederick; Lieneke, Tobias; Schoeppner, Volker (ASPE Spring Topical Meeting)

Reproducibility of the Dimensional Accuracy - Investigations for FDM - Knoop, Frederick; Lieneke, Tobias; Schoeppner, Volker (Summer Topical Meeting 2016)

Dimensional tolerances for additive manufacturing: Experimental investigation for Fused Deposition Modeling - Lieneke, Tobias; Denzer, Vera; Adam, Guido; Zimmer, Detmar (CAT 2016)
Additive manufacturing creates parts in layers without using formative tools. Compared to established manufacturing processes, additive manufacturing offers many advantages. However, only a few research institutions and technology-leading companies use additive manufacturing for end-use part production because relevant challenges have not been sufficiently researched yet. Missing restrictions become apparent in the available geometrical accuracy. The objective of this investigation was the experimental determination of dimensional tolerances using standard parameters. To this end, a methodical procedure was set up. Based on experimentally determined deviations, dimensional tolerances were derived.

Supporting the Decision Process for applying Additive Manufacturing in the MRO Aerospace Business by MADM - Deppe, G.; Koch, R. (27th Annual International Solid Freeform Fabrication Symposium)
The spare part industry in aerospace is highly demanding. For conventional manufacturing technologies it is difficult to meet these requirements. In contrast to that, the design freedom of Additive Manufacturing enables the production of complex and lightweight parts. The lack of experience with this technology hampers the decision where Additive Manufacturing can be economically applied. The cost drivers have to be newly evaluated and holistically investigated. Supply chain advantages have to be considered during the decision process, too. Therefore, aerospace characteristics are analyzed within the paper and a methodology based on Multi Attribute Decision Making (MADM) is introduced. To do so, the cost appraisal for Additive Manufacturing has to be detailed. Additionally, changes in the supply chain have to be identified and quantified. Quality criteria have to be taken into account as well. In the end it is shown how these influence factors can be combined to create a decision support.

Product optimization with and for Additive Manufacturing - Reiher, T.; Koch, R. (27th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing offers a great potential for the optimization of products. Therefore different approaches are feasible to exploit these potentials for elaborating optimal solutions. For example these include optimization of weight or stiffness of structural components as well as the integration of functions and other entities of assemblies. Note, however, that additive manufacturing processes have process specific limitations. Products, components and assemblies, as well as procedures for the design and production preparation must be optimized with regard to a successful additive manufacturing. The use of already known tools for the optimization and design needs to be reconsidered and adapted to theadditive manufacturing. This also includes the production planning with component orientation in build chamber as well as a necessary quality management system. This paper shows several ways for product optimization with additive manufacturing, often based on topology optimization, and procedures for information gathering, decision making and shape determination for part optimization for Additive Manufacturing.

Cost Efficient Design and Planning for Additive Manufacturing Technologies - Lindemann, C.; Koch, R. (27th Annual International Solid Freeform Fabrication Symposium)
Additive manufacturing offers advantages for the production of a final product. Nowadays still many companies have not integrated this new technology into their product development processes (PDP). This paper will discuss additive manufacturing with regards to the current available PDP's while setting a focus on the economic aspects of the integration. Based on a sample part several tools will be discusses which may be uses in the different phases of product development. These tools aim on the simplification of integrating additive manufacturing technologies into existing PDP's. Included are methods for early and accurate cost estimation as well as product selection processes, best practice templates for creating knowledge and process awareness.

Scenario Based Outlook of Additive Manufacturing Applications for the Aerospace Market - Lindemann, C.; Deppe, G.; Koch, R.
Additive Manufacturing (AM) has been growing rapidly with doubledigit growth rates during the last years and a rising trend towards end products. The further development of the technology highly depends on some critical success factors. For the future, it is vital to know which innovations will be necessary to satisfy the needs of industry. The impulsive forces will be those branches whose special characteristics are met by AM. Within the DMRC study “Thinking ahead the Future of Additive Manufacturing – Analysis of Promising Industries” (Gausemeier 2011), especially aircraft production, automotive production and the electronics industry have been identified as very promising to profit from the use of AM. Experts have selected these branches by assessing the prospective attractiveness of current application fields. Those branches are characterized by low quantities, complex part designs, lightweight design and/or high unit prices. For the aerospace industry, all four elements are of high relevance, which is why it has been a pioneer in applying and developing AM technology since the early beginning (Gausemeier 2011 and 2012).

Prevention of Product Piracy - Potentials of Additive Manufacturing - Jahnke, U.; Koch, R.
Additive Manufacturing (AM) is often deemed to be a driver for product piracy in public media. The reasons for this are mainly seen in the fact that it provides a possibility to easily copy three-dimensional objects when used in combination with scanning technologies. This contribution will not focus on the knowledge and skills needed to master AM technology but on its potential contribution to prevent product piracy and reverse engineering. The reverse engineering process will be analyzed to understand the practice of imitators and to transfer the characteristics of AM into specific measures. Finally a five-step methodology is presented which can be used as a guideline to implement protection measures in products to be (re-) developed. This guideline is supposed to be used by industrial companies since an expert survey has identified them as being very likely to profit from the use of AM (Echterhoff et al. 2011).

Combining material efficiency and part reliability by product optimization applying additive manufacturing - Reiher, T.; Deppe, G.; Koch, R. (International Conference Production Engineering and Management 2016)
Nowadays, the material efficiency and part reliability are two majorissues in product development. Thus a product optimization often requires complex structures that are hard to be manufactured conventionally. Additive Manufacturing (AM) however offers great potentials for producing complex shaped parts economically. Different approaches are feasible to exploit these potentials based on the part’s application from shape optimization of structural components to the integration of functions and other entities of assemblies. Several parameters are defined that influence the costs and quality of the future product and carefully have to be balanced. To do so, the use of already known tools for the optimization and design needs to be reconsidered and adapted to the special characteristics of AM. As not all optimization potentials can be realized perfectly, a decision methodology is required to obtain the relevant potentials and to get to a trade-off between all requirements including the ecological impact. The paper shows different approaches for product optimization with AM and procedures for decision making in order to get to the optimal solution.

Unterstützung des AM Entscheidungsprozesses in der Luftfahrtersatzteilversorgung - Deppe, G.; Koch, R. (Rapid Tech 2016)
Additive Fertigungsverfahren bieten in der Luftfahrtindustrie großes Potential. Die Geometriefreiheit ermöglicht die Produktion von komplexen und gewichtsoptimierten Bauteilen. Die mangelnde Erfahrung der Unternehmen mit dieser Fertigungstechnologie erschwert jedoch die Entscheidung, an welcher Stelle Additive Manufacturing ökonomisch sinnvoll eingesetzt werden kann. Die Kosteneinflussfaktoren unterscheiden sich an vielen Stellen von denen traditioneller Fertigungsverfahren und müssen gänzlich neu bewertet und eingeordnet werden. Dabei verlagert sich auch der Fokus weg von den reinen Herstellkosten hinzu einer ganzheitlichen Kostenbetrachtung. Wesentliche Vorteile lassen sich auch meist in der Supply Chain erzielen und müssen im Zuge des Entscheidungsprozesses für ein Fertigungsverfahren bei einem bestimmten Bauteil berücksichtigt werden. Daher werden in der Präsentation die Charakteristika der Luftfahrt analysiert und die Methodik einer Entscheidungsunterstützung vorgestellt. Im Zuge dessen gilt es die Kostenbewertung additiver Fertigungsverfahren näher zu beleuchten, um die Fertigungs- bzw. Reperaturkosten mit traditionellen Verfahren vergleichen zu können. Weiterhin müssen Veränderungen in der Supply Chain identifiziert und bewertbar gemacht werden. Qualitätskriterien müssen ebenfalls mit in die Betrachtung einbezogen werden. Anschließend wird aufgeziegt wie diese Einflussfaktoren in die Entscheidungsunterstützung integriert sind.

Data Management for additive manufacturing: survey on requirements and current state - Gräßler, I.; Taplick, P.; Pottebaum, J.; Scholle, P.; Reiher, T. (14th International DESIGN Conference 2016)
The paper gives an overview of actually used Additive Manufacturing (AM) data formats and AM data infrastructure. Based on empirical analysis of the actual situation, necessary improvement of data management and exchange formats in context with AM technology is derived. The purpose of this paper is to understand the actual use of data formats and management in the field of AM. The paper draws conclusions based on an empirical analysis of the used data formats dependent on stakeholder groups. The results of the expert survey show a necessity to improve or develop new AM specific data formats.

Fatigue Behavior of FDM Parts Manufactured with Ultem 9085 - Fischer, M.; Schöppner, Volker (27th Annual International Solid Freeform Fabrication Symposium)
The mechanical characterization of fused deposition modeling (FDM) parts is mostly done by static tests. In many applications, parts are also dynamically loaded. Here, fatigue tests can help to identify the expected lifetime of a part. This article discusses the fatigue behavior of FDM specimens manufactured with Ultem 9085. For this, tensile bars are manufactured according to ASTM D638 in different build orientations. Tests are performed in a range of pulsating tensile stresses, and S-N curves are documented for different build orientations. For higher loads, the FDM anisotropy characterizes the lifetime of used specimens, which is similar to static tensile bars. For lower loads, including a higher number of cycles to failure, S-N curves of different build orientations converge. In further tests, tensile bars were chemically smoothed with chloroform vapor. Chemical smoothing reduces surface roughness and increases tensile strength of specimens in the upright build direction. Fatigue tests of chemically treated specimens show no significant lifetime increase.